Accidents in Malaysian Construction Industry: Statistical Data and Court Cases - Chong, Heap Yih; Low, T. (Taylor and Francis group, 2014)
Safety and health issues remain critical to the construction industry due to its working environment and the complexity of working practises. This research attempts to adopt 2 research approaches using statistical data and court cases to address and identify the causes and behavior underlying construction safety and health issues in Malaysia. Factual data on the period of 2000–2009 were retrieved to identify the causes and agents that contributed to health issues. Moreover, court cases were tabulated and analyzed to identify legal patterns of parties involved in construction site accidents. Approaches of this research produced consistent results and highlighted a significant reduction in the rate of accidents per construction project in Malaysia.